THERMOPHILIC BACTERIA FROM THE HOT SPRINGS OF GILGIT (PAKISTAN) - M. M. Javed; S. Zahoor; H. Sabar; I. U. Haq; M. E. Babar (Journal of Animal and Plant Sciences, 2012)
The importance of thermostable biomolecules in the field of biotechnology has spurred research into organisms capable of growth at high temperatures. Three thermophilic bacterial strains GCTP-1, GCMB-1 and GCDP-1 were isolated from the hot springs of Tatta Pani, Murtazabad & Darkut Pass respectively in the surroundings of Gilgit.  All isolates have entire and slimy colonies while the cells were small rods, gram-negative non-motile and semi aerobic. Strains GCTP-1 showed positive results of ortho nitrophenyl-β-D-galactopyranosidase (ONPG) and gelatin hydrolysis (GEL) tests other isolates gave negative results in all tests such as ortho nitrophenyl-βD-galactopyranosidase, arginine dihydrolases, lysine decarboxlase, ornithine decarboxylases, citrate utilization, H2S production, urease, tryptophan deaminases, indole production, acetoin production, gelatin hydrolysis, Fermentation/oxidation (glucose, mannitol, inositol, sorbitol, rhamnose, sucrose, melibiose, amygdalin, arabinose) and  cytochrome oxidase. All isolates were grown well at pH range 7–9, with optimum pH 7.2. However, isolates were highly thermophilic and showed optimum growth temperature 65- 70oC
Keywords: Thermophiles; Pakistan; Bacterial strains; hot springs.